PENINGKATAN KECERDASAN LINGUISTIK MELALUI BERMAIN MUSIK (Penelitian Tindakan Anak Usia 4-5 Tahun di PAUD AMRINA Tahun 2018) - Santa Idayana Sinaga (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The purpose of this study is to describe the process of applying music play and to know the improvement of linguistic intelligence of children aged 4-5 years through playing music. This study was conducted on group A children of 17 people. This research is action research with Kemmis and Taggart method which consist of 4 stages namely (plan, action, observation and reflection). This study consists of 2 cycles of each cycle of 8 meetings. Data collection techniques use observation, field notes, and documentation. Data analysis using quantitative and qualitative. Quantitative data analysis is done with statistical descriptions to compare pre cycle to cycle II. The stages of qualitative analysis are data reduction, data display and verification. The results showed that there was an increase in linguistic intelligence through playing music with score on pre cycle 33.8 increasing to 50,4 in cycle I, and experiencing increase of 60,7 in cycle II with very good developing category